2021
DOI: 10.3390/ijms22052327
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy-Sensitive G-Actin Segment 227-235 Is Involved in Salt-Induced Stabilization of Contacts within the Actin Filament

Abstract: Formation of stable actin filaments, critically important for actin functions, is determined by the ionic strength of the solution. However, not much is known about the elements of the actin fold involved in ionic-strength-dependent filament stabilization. In this work, F-actin was destabilized by Cu2+ binding to Cys374, and the effects of solvent conditions on the dynamic properties of F-actin were correlated with the involvement of Segment 227-235 in filament stabilization. The results of our work show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
(165 reference statements)
1
4
0
Order By: Relevance
“…The addition of Cu 2+ ions induced short filaments (Fig. 2C), consistent with electron microscopy of Cu-treated actin filaments [36]. These filaments were notably shorter than those observed in the presence of the formin DIAPH2, one of the human Diaphanous-related formins, which generally accelerate both actin filament nucleation and elongation in the presence of profilin [52].…”
Section: Copper Ions Alter Actin Filament Morphologysupporting
confidence: 80%
See 1 more Smart Citation
“…The addition of Cu 2+ ions induced short filaments (Fig. 2C), consistent with electron microscopy of Cu-treated actin filaments [36]. These filaments were notably shorter than those observed in the presence of the formin DIAPH2, one of the human Diaphanous-related formins, which generally accelerate both actin filament nucleation and elongation in the presence of profilin [52].…”
Section: Copper Ions Alter Actin Filament Morphologysupporting
confidence: 80%
“…In vitro, it was found that Cu 2+ binds with subpicomolar affinity to monomeric actin through Cys374, an interaction that still allows actin to polymerize into filaments [33]. Electron microscopy studies showed that Cu 2+ ions induce fragmentation of actin filaments, leading to shorter filaments but not complete depolymerization [36]. The Cu-binding properties of MT-3 have been linked to its neuronal protective abilities: MT-3 can swap its bound Zn 2+ for Cu 2+ that is bound to neurologically important peptides like amyloid-b peptides, a-synuclein, and prion protein, thereby eliminating harmful redox chemistry associated with copper [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…However, actin filament is very dynamic, and its conformational state is critical for effective contraction. There are multiple mutations in actin responsible for nemaline myopathies; this forms the basis of the study by J. Gruszczynska-Biegala, S. Khaitlina, H. Strzelecka-Gołaszewska et al [3]. The authors provide experimental evidence for the involvement of Segment 227-235 of actin in salt-induced stabilization of contacts within the actin filament and suggest that these contacts can be weakened by mutations characteristic of actin-related myopathies.…”
mentioning
confidence: 88%
“…In F‐actin, the C‐terminus helps to form the interprotomer interface (Holmes, Popp, et al, 1990; Kim et al, 2000; Kim & Reisler, 1996; Śliwińska, Skórzewski, & Moraczewska, 2008), with changes at this interface affecting filament stability (Drewes & Faulstich, 1993; Gruszczynska‐Biegala et al, 2021; Isambert et al, 1995; Kim & Reisler, 2000; Merino et al, 2020; Orlova, Prochniewicz, & Egelman, 1995). For example, the removal of three C‐terminal residues is lethal in yeast (Aspenström, Schutt, Lindberg, & Karlsson, 1993), and proteolytic cleavage destabilizes filaments which makes them more fragile under EM with irregular curvature and filament bundling (Drewes & Faulstich, 1993; Mossakowska, Moraczewska, Khaitlina, & Strzelecka‐Golaszewska, 1993; O'Donoghue, Miki, & dos Remedios, 1992; Orlova & Egelman, 1995).…”
Section: Actin's C‐terminusmentioning
confidence: 99%
“…PDB ID 5MVA was used for panels (a) and (b), PDB ID 8A2Y was used for panel (c). Gruszczynska-Biegala et al, 2021;Isambert et al, 1995;Merino et al, 2020;Orlova, Prochniewicz, & Egelman, 1995). For example, the removal of three C-terminal residues is lethal in yeast (Aspenström, Schutt, Lindberg, & Karlsson, 1993), and proteolytic cleavage destabilizes filaments which makes them more fragile under EM with irregular curvature and filament bundling (Drewes & Faulstich, 1993;Mossakowska, Moraczewska, Khaitlina, & Strzelecka-Golaszewska, 1993;O'Donoghue, Miki, & dos Remedios, 1992;.…”
Section: C-terminal Functional Rolesmentioning
confidence: 99%